2002
DOI: 10.1007/s00402-002-0409-4
|View full text |Cite
|
Sign up to set email alerts
|

The biological and biomechanical effect of different graft tensioning in anterior cruciate ligament reconstruction: an experimental study

Abstract: The objective of the present animal experimental study was to determine the effect of initial graft tension (1 N, 7.5 N, 17.5 N) on the biomechanical and histological behavior of the anterior cruciate ligament (ACL) graft using a rabbit model. After 2, 8, and 32 weeks, the femur-ACL-tibia complex was removed, and biomechanical and histomorphometrical studies were performed. The morphometric parameters cellularity, cell nucleus volume, and vascularity increased up to the 8th postoperative week and showed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…At any rate, the adhesive did appear to have a positive biological effect on tendon-to-bone healing as evidenced by superior histologic, radiographic, and biomechanical results at 6 weeks. The average ultimate load-to-failure for the limbs receiving the bone adhesive at 6 weeks was 71.8 ± 31.8 N, while the average load seen in our previous study with calcium phosphate cement alone at 8 weeks was 38.6 ± 18.0 N. 13 The average ultimate load-to-failure of the native rabbit ACL has been shown in a previous study to be 351.8 ± 41.6 N. 11 Conclusive comparisons cannot be made since these represent historical controls; however, it appears that any augmented healing is still far from re-creating the biomechanics of the native ACL insertion at these time points.…”
Section: Discussionmentioning
confidence: 77%
“…At any rate, the adhesive did appear to have a positive biological effect on tendon-to-bone healing as evidenced by superior histologic, radiographic, and biomechanical results at 6 weeks. The average ultimate load-to-failure for the limbs receiving the bone adhesive at 6 weeks was 71.8 ± 31.8 N, while the average load seen in our previous study with calcium phosphate cement alone at 8 weeks was 38.6 ± 18.0 N. 13 The average ultimate load-to-failure of the native rabbit ACL has been shown in a previous study to be 351.8 ± 41.6 N. 11 Conclusive comparisons cannot be made since these represent historical controls; however, it appears that any augmented healing is still far from re-creating the biomechanics of the native ACL insertion at these time points.…”
Section: Discussionmentioning
confidence: 77%
“…The conclusions of the study by Yoshiya et al stand in contrast to those of Labs et al who found superior biomechanical strength of BPTB grafts tensioned at 17.5N compared with those reconstructed with 1N of tension in rabbits. 11 The results of Labs et al not only demonstrated better load-to-failure strength, but also improved morphology of the ACL graft itself in the higher tensioned group. Abramowitch et al similarly evaluated ACL pretension and graft healing in goats.…”
Section: Discussionmentioning
confidence: 94%
“…3 Similar to human studies, the results of animal studies on ACL graft pretension have been mixed. 1,10,11 An important limitation is an absence of studies that have evaluated the effect of different graft pretension levels on soft tissue ACL autografts, which is the most common graft chosen for human reconstruction. Furthermore, studies that have been performed have mainly focused on load-to-failure properties, as well as the ACL graft maturation process.…”
mentioning
confidence: 99%
“…Due to the composite nature of the graft, it appears essential to apply equal tension to all the strands during tibial fixation [8,15]. This, it is suggested, will provide optimal strength and stiffness to the graft leading to a better surgical outcome [5,6,22]. It is further proposed that any disparity in the tension between strands may lead to disproportionate tensile loading and which, may ultimately lead to early rupture of the strands, weakening the entire reconstruction.…”
Section: Discussionmentioning
confidence: 99%